A Correlation Evaluation Between the Peripheral Blood Index and the Prognosis of Advanced Esophageal Squamous Cell Carcinoma Patients Treated with Camrelizumab - Shang H; Chen Y; Wang Q; Yang Y; Zhang J (Dove Medical Press, 2024)
Haotian Shang, Yanan Chen, Qiulu Wang, Yongliang Yang, Jingyu Zhang Department of Oncology, Clinical College of Second People's Hospital of Lianyungang, Bengbu Medical College, Lianyungang, People's Republic of ChinaCorrespondence: Jingyu Zhang, Department of Oncology, Clinical College of Second People's Hospital of Lianyungang, Bengbu Medical College, No. 41, Hailian East Road, Haizhou District, Lianyungang City, Jiangsu Province, People's Republic of China, Email zhangjingyu@njmu.edu.cnPurpose: This study aimed to investigate the relationship between peripheral blood indices and the efficacy and prognosis of advanced esophageal squamous cell carcinoma (ESCC) patients treated with camrelizumab.Patients and Methods: We retrospectively analyzed 64 patients who received camrelizumab for advanced ESCC at the Second People's Hospital of Lianyungang City between July 2020 and June 2022. The study included examination of the neutrophil-to-lymphocyte ratio (NLR), the platelet-to-lymphocyte ratio (PLR), the systemic inflammation index (SII), the lymph-to-monocytes ratio (LMR), the absolute lymphocyte count (ALC), and lactate dehydrogenase (LDH). We used multivariate logistic regression analysis to explore the link existing between peripheral blood and the efficacy of treatment. Determination of potential prognostic factors for Progression-free survival (PFS) and Overall survival (OS) using Cox regression analysis. The nomogram model was developed based on the results of the Cox multivariate analysis. Patients were divided into three groups according to the reduction in LDH and LDL levels before treatment, and the Kaplan-Meier survival curves for the three groups were compared and ROC curves for LDH combined with PLR were plotted.Results: Lower LDH (OR=6.237, 95% CI: 1.625- 23.944) were independently associated with disease control rates(DCR). LDH was independently correlated with PFS (HR: 0.227 95% CI: 0.099- 0.517). LDH and PLR were independently linked to OS. The C index of the nomogram model is 0.819, indicating good predictive performance. Kaplan-Meier Survival Curve suggested better OS in patients with reduced pretreatment LDH and PLR. The area under the ROC curve showed that the LDH index combined with the PLR index predicts patient survival better than the index alone.Conclusion: LDH combined with PLR predicted prognosis in patients with ESCC treated with camrelizumab.Keywords: esophageal squamous cell carcinoma, camrelizumab, immunotherapy, peripheral blood, prognostic index